The roles of oncogenic miRNAs and their therapeutic importance in breast cancer. (February 2017) - O'Bryan, Samia; Dong, Shengli; Mathis, J. Michael; Alahari, Suresh K.
Abstract: Since the discovery of tumour suppressive miRNA in 2002, the dysregulation of miRNAs was implicated in many cancers, exhibiting both tumour suppressive and oncogenic roles. Dysregulation of miRNAs was found to be involved in the initiation of oncogenesis, as well as the progression, invasion and metastasis of cancers. While normal miRNA inhibitory functions help regulate gene expression in the cell, oncogenic miRNA, when dysregulated can lead to suppression of critical pathways that control apoptosis, cell cycle progression, growth and proliferation. This suppression allows for the upregulation of pro-oncogenic factors that drive cell survival, growth and proliferation. Due to emerging discoveries, oncogenic miRNAs are proving to be a critical component in cancers, such as breast cancer, and may provide novel avenues for cancer treatment. In this article, we discuss the roles of the most studied oncogenic miRNAs in breast cancer including clusters and families involved as well as the less studied and recently discovered oncogenic miRNAs. These miRNAs provide valuable information into the complexity of regulatory elements affected by their overexpression and the overall impact in the progression of breast cancer. Also, identifying miRNAs causing or leading to resistance or sensitivity to current anti-cancer drugs prior to treatment may lead to an improvement in treatment selection and overall patient response. This review summarizes known and recently discovered miRNAs in literature found to have oncogenic roles in breast cancer initiation and the progression, invasion and metastasis of the disease. Highlights: Important role of microRNAs in breast cancer is depicted. Therapeutic importance of microRNAs is assessed. Mechanistic view of microRNA regulation in breast cancer is discussed.